Understanding Research Methodology and Adversity Quotient on Students' Ability to Compose Theses in the 2019 PIPS Department, Jambi University - Dearti Dearti; Rosmiati Rosmiati; Mayasari Mayasari (Badan Pengelola Usaha (BPU) Universitas Jambi, 2023)
This research aims to determine the influence of understanding research methodology and the Adversity Quotient on students' ability to prepare theses in the PIPS Department Class of 2019, Jambi University, both partially and simultaneously. This research is research with a quantitative approach using a survey method. The results show that the variable understanding research methodology has a positive and significant effect on understanding research methodology and the adversity quotient has a positive and significant effect on students' ability to compose a thesis with the F test value, Fcount>Ftable value, namely 25.430 > 3 .06 with a sig value of 0.000 < 0.05 and a coefficient of determination (R2) value of 0.265 or 26.5%.